Assessment of safety culture by surgical unit nursing teams - Marinho,Monique Mendes (2014)
The objective was to evaluate the patient safety culture from the perspective of the nursing teams at two surgical inpatient units of a university hospital, using the Safety Attitudes Questionnaire. Cross-sectional survey with quantitative approach, conducted at the two surgical inpatient units of the university hospital in Florianópolis, SC, Brazil. The Safety Attitudes Questionnaire was applied to 46 nursing professionals. Data analysis used descriptive and inferential statistics. The results show that all dimensions measured values scored lower than the minimum positive safety culture. The lower scores were found in the dimensions "perceptions of management" and "working conditions". Concerning the age of the professionals, young professionals stood out with higher scores. As for the professional categories, the higher scores were related to nursing assistants. The evaluation of the safety culture in the units studied demonstrates weakness in the six dimensions assessed.